ROLE OF INTERNATIONAL COURT OF JUSTICE AND ITS LEGALLY BINDING ADVISORY OPINIONS IN DEALING WITH ARMED CONFLICTS - Rezara, Juvelin (Badan Pembinaan Hukum Nasional Kementerian Hukum Republik Indonesia, 2024)
Advisory opinion is an alternative resolution of conflict in the international court of justice (hereinafter ICJ). The opinion is commonly requested in armed conflict issue; It consists of an advice by interpreting the international principles based on the concept of the “Jus ad bellum” and “Jus in bello”. Nevertheless, the ICJ statute does not determine conspicuously the legal binding of the opinion. This research ostensibly sought to highlight the legal force of the opinion. Hence, what is exactly the value of ICJ`s opinion in armed conflict? This question demands evidently a doctrinal approach and analysis of cases. This study mainly pointed out the conditions for requesting the advisory opinion, and the analogy of its legal binding effect. Certainly, this resolution might have legal effect but it depends on the circumstances. As a result, it might be crucial for resolving the contemporary armed conflict over the world.